Apparent digestibility and gut integrity of chicken fed a diet supplemented with African safou (Dacryodes edulis) - Tangomo, A.N.; Gicheha, M.G.; Kagira, J.M.; Tiambo, Christian K. (Science Alert, 2021)
Background and Objective: In the present study, which is the second in a series of three publications on a project aimed at evaluating the efficacy and safety of utilizing African Safou (Dacryodes edulis) in poultry feeds as an additive, the goal was to determine the apparent digestibility and gut integrity of chicken fed a diet supplemented with Dacryodes edulis parts. The first paper explored the impact of the plant parts on growth traits, ceca microbiota and blood parameters in dual-purpose indigenous chicken. Materials and Methods: In the current study, a total of 288 male dual-purpose indigenous chicken were fed six experimental diets. The diets differed in terms of the D. edulis part that was included plus its inclusion level. Data on the growth performance of the chicken fed the experimental diets were compared to chicken fed a positive (T+) and a negative (T¯) control diet. The chickens were fed the diets for a period of 14 weeks. The apparent digestibility variability of various nutrients and gut morphometric variables were measured using standard methods. Data were collected and analyzed. Results: All the experimental diets improved the apparent digestibility of metabolizable energy (AME), dry matter (DM), fat, crude protein (CP), crude fiber (CF) and calcium . Conversely, the values for zinc, magnesium and phosphorus were negative. The AME, DM content and fat digestibility differed significantly between and among treatment diets. The gut morphometric variables were not significantly different across the treatment groups. Conclusion: The findings obtained in this study showed that parts of D. edulis plant positively impacted the apparent digestibility of the feed.